(untitled) (Journal of Biomedical Investigation, 2025)
Background: The threat of antiretroviral drug resistance developing and spreading is of greater public health importance as antiretroviral therapy is scaled up. Therefore, this study was designed to assess the growing contribution to Africa’s antiretroviral drug resistance Research. Materials and Methods: This investigation presents a bibliometric analysis of all research articles on antiretroviral drug resistance published from May, 2004 to May 2024, indexed in the PubMed database. Result: The overall number of articles published was 1,601 papers, which has an average annual productivity of 123.15. South Africa accounted for the highest productive outputs with the total number of publications of 216, followed by the Switzerland (n = 56), Uganda (n = 52), Kenya (n = 18), Zimbabwe (n = 18), Netherlands (n = 15), Cameroon (n = 12), Botswana (n = 10), Malawi (n = 10), Zambia (n = 6), Ethiopia 6 (n = 6), and Nigeria (n = 5). Since 2015, publications on ARV Drug Resistance Research have fluctuated, with the highest number in 2020. Following that trend, the number of productive outputs dramatically reduced from 2021 to 2024. The University of Cape Town, South Africa, emerged as the leading institution in ARV Drug Resistance Research. In Nigeria, ARV Drug Resistance Research is the least prolific. Conclusion: The overall trend in this field is characterized as decreasing yet evolving. This suggests that while fewer studies are being published overall, the focus of the research is shifting, likely toward these previously understudied areas rather than repeating established research.